The Application of Technological Intervention for Stroke Rehabilitation in Southeast Asia: A Scoping Review With Stakeholders' Consultation - Selamat, Siti Nur Suhaidah; Che Me, Rosalam; Ahmad Ainuddin, Husna; Salim, Mazatulfazura S. F.; Ramli, Hafiz Rashidi; Romli, Muhammad Hibatullah (Frontiers in Public Health, 2022)
Background: The technological intervention is said to be an adjunct to the conventional therapies applied in the rehabilitation session. In most high-income countries, technology has been widely used in assisting stroke patients to undergo their treatments. However, in Southeast Asia, the use of technology is still lacking especially in middle- and low-income countries. Thus, this scoping review identifies and summarises the effectiveness of technological intervention in helping the recovery of stroke survivors during stroke rehabilitation in Southeast Asia. Methods: The JBI manual for evidence synthesis was used to conduct a scoping study. Up until September 2021, an electronic search was performed using four databases (Medline, CINAHL, Scopus, ASEAN Citation Index). Only the studies that were carried out in Southeast Asia were chosen. Results: Forty-one articles were chosen in the final review from a total of 6873 articles found during the initial search. Most of the studies reported the implementation of technological intervention combined with conventional therapies in stroke rehabilitation. Singapore has the most studies that implemented technological interventions followed by Thailand, Malaysia and Indonesia. The majority of the studies show that the use of technological interventions can enhance the recovery period of stroke patients. The consultation session suggested that the technological interventions should facilitate the needs of patients, practitioners, and caregivers during the rehabilitation. Conclusions: The integration of technology into the conventional methods has shown a positive outcome as it can show significant improvement during stroke recovery. Future studies are recommended to investigate the potential of home-based technological intervention, as well as for lower extremities.